On Single-Valued Neutrosophic Soft Filter Convergence (Contemporary Mathematics, 2024)
The concept of single-valued neutrosophic soft filters plays a crucial role in the study of topological spaces. Extensive research has led to several generalizations of these filters, highlighting their significance in neutrosophic theory. This paper introduces a novel approach to single-valued neutrosophic soft filters, along with the idea of single-valued neutrosophic soft quasi-coincident neighborhood spaces, which are characterized by a unique interaction between the filters and quasi-coincident neighborhood structures. Additionally, we explore advanced neutrosophic theories, focusing on the properties and convergence of single-valued neutrosophic soft filters in soft topological spaces. Finally, we demonstrate the existence of product fuzzy soft filters.
Keywords: single-valued neutrosophic soft set; single-valued neutrosophic soft filters; single-valued neutrosophic soft neighborhood; single-valued neutrosophic soft convergence